2023
DOI: 10.1136/bmjopen-2022-064275
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity of cardiometabolic diseases: a cross-sectional study of patterns, clusters and associated risk factors in sub-Saharan Africa

Abstract: ObjectiveTo determine the patterns of cardiometabolic multimorbidity and associated risk factors in sub-Saharan Africa (SSA).DesignWe used data from the WHO STEPwise approach to non-communicable disease risk factor surveillance cross-sectional surveys conducted between 2014 and 2017.ParticipantsThe participants comprised 39, 658 respondents aged 15–69 years randomly selected from nine SSA countries using a multistage stratified sampling design.Primary outcome measureUsing latent class analysis and agglomerativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…Similarly, our previous study on the patterns of cardiometabolic multimorbidity in sub-Saharan Africa identified the clustering of physical inactivity and obesity as one of the leading risk factors for cardiometabolic multimorbidity. However, the study did not include the clustering of cardiometabolic diseases with unrelated conditions such as arthritis, cataract and chronic respiratory diseases [ 54 ]. Importantly, the discordant multimorbidity clusters without well-established pathogeneses such as cardiometabolic diseases and arthritis identified in the current study should be studied in the future to elucidate the causal pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our previous study on the patterns of cardiometabolic multimorbidity in sub-Saharan Africa identified the clustering of physical inactivity and obesity as one of the leading risk factors for cardiometabolic multimorbidity. However, the study did not include the clustering of cardiometabolic diseases with unrelated conditions such as arthritis, cataract and chronic respiratory diseases [ 54 ]. Importantly, the discordant multimorbidity clusters without well-established pathogeneses such as cardiometabolic diseases and arthritis identified in the current study should be studied in the future to elucidate the causal pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In this cross-sectional study, we recruited chronic disease patients who had been diagnosed at Seoul National University Hospital between October 2016 and February 2017. The inclusion criteria were as follows: aged ≥ 19 years, diagnosed with ≥ 1 chronic disease (hypertension 4 , 66 , hyperlipidemia 66 , diabetes 4 , 66 , chronic pulmonary disease 67 , 68 , chronic renal disease 69 , 70 , chronic arthritis 67 , 71 , or osteoporosis 4 , 5 ), visited the outpatient clinic at Seoul National University Hospital between October 2016 and February 2017 for treatment of chronic diseases, fluent in Korean, and willing to participate in this study. A total of 535 adults regularly visited the outpatient clinic for treatment of chronic diseases and completed self-report questionnaires between October 5, 2016 and February 28, 2017.…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review of randomised controlled trials (RCTs) of integrated care for multimorbidity in children and adults in primary care in LMICs identified five RCTs, with only low-certainty evidence found for improvement in systolic blood pressure 27. In sub-Saharan Africa, there was moderate-grade evidence for integrated care models in primary care settings for people with cardiometabolic morbidity 28. A Cochrane review of the interventions for multimorbidity published in 2021 could not make strong recommendations for the care of people with multimorbidity but suggested that organisational changes that target specific problems and align with outcomes of interest specific to the patient could be successful and that more research was needed.…”
Section: Introductionmentioning
confidence: 99%